FAKTOR - FAKTOR YANG MEMPENGARUHI PENGHIMPUNAN DEPOSITO MUDHARABAH PADA PERBANKAN SYARIAH DI INDONESIA - Shifa, Mutiara; Soemitra, Andri; Sugiyanto, Sugiyanto (CV. Publikasi Indonesia, 2022)
The purpose of this study is to identify and analyze the factors that influence the accumulation of deposits in Mudharabah, an Islamic bank in Indonesia. The independent variables in this study are interest rate (X1), inflation (X2) and savings (X3), and the dependent variable is Mudarabah deposits. This study adopts quantitative research method. Quantitative research is research that uses data in numerical form. The results of the study show that interest rates have no significant effect on the mudharabah deposit component of Islamic commercial banks in Indonesia. This means that there is no influence between the interest rate variable (X1) on Mudharabah Deposits, Inflation has a partially significant effect on mudharabah deposits at Islamic Commercial Banks in Indonesia. This means that the Inflation variable (X2) has a significant effect on Mudharabah Deposits, Financing To Deposit Ratio (FDR) has a partially significant effect on mudharabah deposits at Islamic Commercial Banks in Indonesia. This means that the effect of the FDR variable (X3) on Mudharabah Deposits, Interest Rates, Inflation, and FDR simultaneously (simultaneously) has a significant effect on Mudharabah Deposits at Islamic Commercial Banks in Indonesia